2013
DOI: 10.1152/ajpheart.00196.2013
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic cardiac hyperinnervation and atrial autonomic imbalance in diet-induced obesity promote cardiac arrhythmias

Abstract: Obesity increases the risk of arrhythmias and sudden cardiac death, but the mechanisms are unknown. This study tested the hypothesis that obesity-induced cardiac sympathetic outgrowth and hyperinnervation promotes the development of arrhythmic events. Male Sprague-Dawley rats (250-275 g), fed a high-fat diet (33% kcal/fat), diverged into obesity-resistant (OR) and obesity-prone (OP) groups and were compared with rats fed normal chow (13% kcal/fat; CON). In vitro experiments showed that both OR and OP rats exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 43 publications
4
20
0
2
Order By: Relevance
“…These findings of decreased basal parasympathetic tone are consistent with observations of normal cardiac norepinephrine spillover in patients with obesity-related hypertension, despite impaired baroreflex control and increases in sympathetic activity to the kidneys and skeletal muscular vasculature (171). Recently, it was found that the consumption of a high-fat diet in rats, even in the absence of overt obesity, stimulates sympathetic outgrowth and hyperinnervation of the heart (110), and this, together with atrial autonomic imbalance, may promote the development of arrhythmic events.…”
Section: Sns In Obesity and End-organ Damagesupporting
confidence: 86%
“…These findings of decreased basal parasympathetic tone are consistent with observations of normal cardiac norepinephrine spillover in patients with obesity-related hypertension, despite impaired baroreflex control and increases in sympathetic activity to the kidneys and skeletal muscular vasculature (171). Recently, it was found that the consumption of a high-fat diet in rats, even in the absence of overt obesity, stimulates sympathetic outgrowth and hyperinnervation of the heart (110), and this, together with atrial autonomic imbalance, may promote the development of arrhythmic events.…”
Section: Sns In Obesity and End-organ Damagesupporting
confidence: 86%
“…Some reports have shown QT prolongation or an increased late potential in obese patients 23, 24, 25. An autonomic disturbance was reported in obese patients,26 which may provoke arrhythmia.…”
Section: Discussionmentioning
confidence: 98%
“…направлении имеет лишь эпидемиологический харак-тер [2,3]. Детализация механизмов развития ФП у туч-ных людей представляет важную задачу для совре-менной кардиологии, так как эти знания могут спо-собствовать разработке универсальных подходов к лечению данных пациентов.…”
Section: Atrial Fibrillation and Obesity фибрилляция предсердий и ожиunclassified
“…Молекулярные механизмы симпатической гипериннервации миокарда при ожи-рении не установлены. Имеются данные о том, что при-чинами этого могут быть повышение чувствительности TrkA-рецепторов к фактору роста нервов и прямое влияние СЖК плазмы на рост нервов и развитие сим-патической гипериннервации [3].…”
Section: дисбаланс вегетативной регуляцииunclassified